LITHOLOGICAL FEATURES OF PRECAMBRIAN GOLD-BEARING ROCKS: EVIDENCE FROM THE UKRAINIAN SHIELD - Dragomiretskii A.V. (My University, 2004)
Based on traditional petrochemical and nontraditional mineralogical methods (accessory zircon generation analysis), specific features of the primary composition of strongly metamorphosed rocks from some Early Precambrian Au-bearing rocks of the Ukrainian Shield (US) were studied. The confinement of several gold ore occurrences to primarily sedimentary Late Archean rocks of the Ukrainian Shield has been established and the possibility of their chemogenic origin is considered. The joint analysis of plicative tectonics and metamorphism facies in the study area demonstrated that Au-bearing primarily sedimentary (chemogenic) rocks of the Khashchevatoe–Zaval'ev Formation of the Bug Group (AR2) are confined to amphibolite-facies domains within tectonic (high-order synform) structures with a significant gold potential.
Keywords: Gold-Bearing Rocks; Ukrainian Shield; Precambrian::Archean; Докембрий::Архей